APPLYING THE AUDITORY-ORAL METHOD TO IMPROVE THE SPEAKING SKILL OF NINTH-GRADE STUDENTS AT RAYHAN AL-JANNAH BORDING SCHOOL - Nailan Ni'mah Nasution; Ismail Baharuddin; Muhamad Zainulhaq Mafakhir (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2022)
This paper aims to improve speaking skills in Arabic, at the Rayhan Al-Janah Islamic Boarding School. This type of research is Classroom Action Research. This classroom action research is carried out in four stages: planning, implementation, monitoring, and reflection. The sources in this study were thirty students and the evidence was collected using tests and observations. the test results before the action obtained an average of 50.00%, the first trial was 73.33%, and the second trial was 93.33%, due to an increase in the determination of the degree of acquisition from before the trial to the second trial, with an increase of 43, 33%, Students experienced improvement after applying the audio-oral method. These results are applied to the first observation with an average of 59%, the second observation with an average of 68.75%, the third observation with an average of 79.1%, and the fourth observation with an average of 89% تطبيق طريقة السمعية الشفهية لترقية مهارة الكلام لدى تلاميذ الفصل التاسع بمعهد ريحان الغرض من هذا البحث في هذه الحالة هي: لمعرفة الترقية مهارة الكلام باللغة العربية بتطبيق الطريقة السمعية الشفهية بمعهد ريحان الجنة في هذا البحث،  نوع هذا البحث هو بحث العمل الفصل بمعهد ريحان الجنة فاسر ماغا المركزية لمبه سورك مرافي المقاطعة مندئلنج ناتل يعتمد على دورين، مع أربع مراحل هي التخطيط والتنفيذ والمراقبة والانعكاس. ومصادر في هذا البحث ثلاثون الطلاب وجمع البينات بالإستخدام الاختبارات والملاحظات. حصل الاختبار بدون التجريب على متوسط %50،00 والتجريب الأول % 73,33 والتجريب الثاني %93،33، نظرا ترقية في تحديد على درجة الاكتساب من قبل التجريب حتى التجريب الثاني مرتفعا بعدد %43،33. وحصل الطلاب الزيادة بعد تطبيق طريقة السمعية الشفهية. حصل النتائج تطبيق على الملاحظة الأولى بمتوسط % 59 والملاحظة الثانية بمتوسط % 68،75 والملاحظة الثالثة في المتوسط %79،1 والملاحظة الرابعة في المتوسط في المتوسط % 89 وحصل الزيادة عن ملاحظات عند تطبيق طريقة السمعية الشفهية.